Acute generalized exanthematous pustulosis induced by flupentixol-melitracen: a previously unreported drug reaction - Das, Dipanjan; Teza, Lairenjam; Gangopadhyay, Asok (International Journal of Basic & Clinical Pharmacology, 2025)
Acute generalized exanthematous pustulosis (AGEP) is a rare and severe cutaneous drug reaction, most often triggered by antibiotics or antifungals. Psychotropic medications are an uncommon cause. We report the case of a 60-year-old male who developed AGEP within 24-48 hours of initiating flupentixol-melitracen, a fixed-dose antipsychotic-antidepressant combination. Clinical features included widespread sterile pustules on an erythematous base, and histopathology confirmed the diagnosis. The eruption resolved rapidly upon drug withdrawal and topical corticosteroids. To the best of our knowledge, this is the first reported case of AGEP induced by flupentixol-melitracen. Clinicians should consider this rare association when evaluating drug-induced pustular eruptions.